2014
DOI: 10.14202/vetworld.2014.95-99
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, characterization and antibiogram of Pasteurella multocida isolated from pigs in Mizoram with special reference to progressive atrophic rhinitis

Abstract: How to cite this article: Varte Z, Dutta TK, Roychoudhury P, Begum J and Chandra R (2014) Isolation, identification, characterization and antibiogram of Pasteurella multocida isolated from pigs in Mizoram with special reference to progressive atrophic rhinitis, Veterinary World 7(2): 95-99. Introductionfor induction of the experimental disease, development of improved diagnostics, development of effective Progressive atrophic rhinitis (PAR) is a widely therapeutic/ prophylactic pharmaceutical approaches preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Pasteurellosis confirmation seems to be difficult due to multiple clinical symptoms and time-consuming laboratory procedures. Furthermore, it is difficult to obtain a pure culture of PM from clinical isolates because of contaminants and/or death of organisms [ 26 ]. It has been observed that the detection of PM in the clinical material is greatly accelerated by the use of PCR technique and could yield isolation of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurellosis confirmation seems to be difficult due to multiple clinical symptoms and time-consuming laboratory procedures. Furthermore, it is difficult to obtain a pure culture of PM from clinical isolates because of contaminants and/or death of organisms [ 26 ]. It has been observed that the detection of PM in the clinical material is greatly accelerated by the use of PCR technique and could yield isolation of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurellosis is a common disease of pigs worldwide with specific serotype and pathotype associated with the respiratory disease [ 16 - 18 ]. However, the distribution pattern of the serotypes and pathotypes can vary considerably from region to region and over time in a given region [ 12 , 19 ]. The present study results in the detection of more percentage of serotype A than serotype D. The isolates used in the present study were mainly from cases of the respiratory syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A higher percentage of serotype A than serotype D in P. multocida isolates from indigenous pigs in central Kalorey et al . [ 20 ] and Northeast India [ 19 , 21 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the toxA gene is a virulence gene associated with P. multocida, was identified by PCR in all isolates. A previous investigation reported that PCR targeting toxA gene is sensitive and essential for the detection of pathogenic P. multocida (Varte et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The P. multocida strains were exposed to the pathogenicity test as the previously described protocol (Varte et al 2014). Briefly, six mice were I/P inoculated with 100 μl of the whole culture; in addition, three mice were inoculated with 100 μl of sterile H 2 O (control group).…”
Section: Pathogenicity Test Of the Isolated P Multocida Strainsmentioning
confidence: 99%